PENGEMBANGAN KAMPANYE DIGITAL UNTUK MENINGKATKAN BRAND EQUITY LEMBAGA KONSULTAN KEUANGAN FINOLOGI - Muhammad Syihabuddin; Astuti Wulandari; Dika Puspitaningrum (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service program aims to provide guidance in developing a digital campaign to strengthen the brand equity of the financial consulting firm Finologi. In the financial services industry, brand equity is a strategic factor that determines long-term success, as trust and credibility are the foundation of client relationships. However, Finologi faces challenges such as low brand awareness and a lack of service differentiation compared to competitors. Through this program, a series of activities were conducted, including initial observation, introduction to brand equity concepts, workshops on digital campaign strategies, and assistance in drafting a campaign plan. The focus was on enhancing the internal team’s understanding of brand awareness, brand association, perceived quality, and customer loyalty. The outcomes include an initial digital campaign plan consisting of financial education content, service storytelling, and distribution strategies for key platforms (LinkedIn, Instagram, TikTok, and the company website). With this guidance, Finologi is expected to independently implement its digital campaign to strengthen brand positioning, improve competitiveness, and build sustainable client relationships.